The building blocks and origins of life - Bellstedt, Dirk U. (HTS teologiese studies, 2020)
The building blocks and origins of life have fascinated scientists since the earliest of times. What is required for life to work in terms of building blocks? An outline of the building blocks that have to be present in living systems to allow the processes that are required for life is given. These building blocks have to be organised in a specific way to allow living processes to be functional, which are summarised in what is referred to as the seven pillars of life. In essence, these are the fundamental characteristics of all living systems. Evidences of when and how living systems developed on the Earth shortly after the Earth established itself as a planet are discussed. This comes from the growing body of geological evidence of the age of rocks and rock formations in different places on the Earth. This review is concluded with the latest evidence of where on Earth living systems may have started. A large amount of uncertainty exists about these processes, but more and more consilient evidence is giving us important pointers as to the origins of life on the planet Earth.Contribution: As part of this special collection, the building blocks or origins of life give insights into the chemical principles and constituents of living organisms and how their interactions allow life to function on earth.